Formin-like 2 drives amoeboid invasive cell motility downstream of RhoC - Kitzing, Thomas; Wang, Ying; Pertz, O.; Copeland, J. W.; Grosse, R. (Oncogene, 2010)
Invasive cell migration is a key step for cancer metastasis and involves Rho GTPase-controlled reorganization of the actin cytoskeleton. Altered Rho GTPase expression is found in various malignancies. Particularly, the closely related GTPases RhoA and RhoC are upregulated in many aggressive tumours, but specific effectors that distinguish between these two GTPases to explain mechanistic differences have not been identified. The formins are by far the largest family of Rho GTPase effectors and are characterized by the actin-nucleating formin homology 2 domain. Using siRNA-based screening against all 15 human formins, we systematically analysed their functions in 3D cell motility using three different cancer cell lines. These results reveal distinct requirements for specific formins in amoeboid versus mesenchymal invasive cell migration. Importantly, by knocking down all Rho proteins, we identified formin-like 2 (FMNL2) as a specific RhoC effector, showing selective interaction of FMNL2 with active RhoC, but not RhoA or RhoB. Functional analysis shows that RhoC regulates autoinhibition of FMNL2, whereas suppression of FMNL2 inhibits RhoC-, but not RhoA-dependent, rounded invasive cell migration. Thus, our data uncover a novel regulatory and functional interaction between RhoC and FMNL2 for modulating cell shape and invasiveness and provide mechanistic insight into RhoC-specific signalling events.
Gesehen am 14.03.2023